Ketogenic Diet for the Treatment and Prevention of Dementia: A Review. (January 2021) - Davis, Joshua J.; Fournakis, Nicole; Ellison, James
Dementia (major neurocognitive disorder) is an increasingly common syndrome with a significant burden on patients, caregivers, the health-care system, and the society. The prevalence of dementia will certainly continue to grow as the US population ages. Current treatments for dementia, though, are limited. One proposed nonpharmacologic approach for the delay or prevention of dementia is the use of a ketogenic diet. The ketogenic diet was originally employed to treat refractory epilepsy and has shown promise in many neurologic diseases. It has also gained recent popularity for its weight loss effects. Several preclinical studies have confirmed a benefit of ketosis on cognition and systemic inflammation. Given the renewed emphasis on neuroinflammation as a pathogenic contributor to cognitive decline, and the decreased systemic inflammation observed with the ketogenic diet, it is plausible that this diet may delay, ameliorate, or prevent progression of cognitive decline. Several small human studies have shown benefit on cognition in dementia with a ketogenic diet intervention. Future, large controlled studies are needed to confirm this benefit; however, the ketogenic diet has shown promise in regard to delay or mitigation of symptoms of cognitive decline.